1986
DOI: 10.1007/bf02429065
|View full text |Cite
|
Sign up to set email alerts
|

Multi-system Coxsackievirus B-6 infection with findings suggestive of diabetes mellitus

Abstract: A fatal case of Coxsackievirus B-6 (CBV-6) infection in a 4 1/2-year-old girl is reported. The disease was initially characterized by a severe meningoencephalitis and, successively, by the appearance of hyperglycaemia and glycosuria, concomitantly with complement-fixing-islet cell antibodies (CF-ICA) and ICA, diarrhoea, electrolyte disorders, arrhythmia and decrease of the IgG levels, suggesting a multi-system involvement. CBV-6 was identified by isolation from stool and cerebrospinal fluid and by detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…A predisposing, multigenic component has been described but accounts for fewer than 50% of cases (7,35,45); environmental factors (e.g., viral infections) have therefore been proposed to explain the remaining cases of T1D (3,6,32,57,58) that cannot be ascribed solely to host-driven pathogenic autoimmunity. Human enterovirus (HEV) infections have long been suspected as environmental triggers of human T1D (12,22,27); infections by common HEVs, such as the group B coxsackieviruses (CVB 1 to 6) and diverse echoviruses, have been implicated as triggers of T1D onset at the time of or shortly after infection (8,9,13,19,28,37,39,40,42,52,60). Nonetheless, it remains unclear whether HEV initiates T1D in humans (18,21,24,26); evidence supporting an etiologic connection between HEV infection and T1D onset is not as well-established as the links between, for example, specific HEV infections and poliomyelitis, aseptic meningitis, or myocarditis (43).…”
mentioning
confidence: 99%
“…A predisposing, multigenic component has been described but accounts for fewer than 50% of cases (7,35,45); environmental factors (e.g., viral infections) have therefore been proposed to explain the remaining cases of T1D (3,6,32,57,58) that cannot be ascribed solely to host-driven pathogenic autoimmunity. Human enterovirus (HEV) infections have long been suspected as environmental triggers of human T1D (12,22,27); infections by common HEVs, such as the group B coxsackieviruses (CVB 1 to 6) and diverse echoviruses, have been implicated as triggers of T1D onset at the time of or shortly after infection (8,9,13,19,28,37,39,40,42,52,60). Nonetheless, it remains unclear whether HEV initiates T1D in humans (18,21,24,26); evidence supporting an etiologic connection between HEV infection and T1D onset is not as well-established as the links between, for example, specific HEV infections and poliomyelitis, aseptic meningitis, or myocarditis (43).…”
mentioning
confidence: 99%
“…It was suggested that the virus invaded the pancreas and destroyed pancreatic b cells by viral cytolysis. Repeatedly, CVB antigens have been found in b cells after fatal infections [37,38] failed to demonstrate enterovirus antigens in the pancreas [39,40]. In vitro studies reported that about 30% of CVB serotype 4 strains have tropism for the murine pancreas [11], while other serotypes (CVA serotypes 7 and 9 and CVB serotype 5) have been shown to destroy mouse b cells as well [12].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of autoantibodies to the protein tyrosine phosphatase (IA-2) and islet cell antigen were measured by validated methods as described elsewhere [29]. The presence of antibodies to a glycosylated islet cell membrane antigen (GLIMA 38 NOTE. List of molecular mimicry peptides that were tested in a lymphocyte proliferation assay.…”
Section: Patient Materials and Methodsmentioning
confidence: 99%
“…Much of the evidence has come from epidemiological studies linking recent-onset IDDM with coxsackie B virus infections (reviewed in Yoon & Kominek, 1995). In addition to epidemiological studies, there have been several case reports in which coxsackie B viruses have been isolated from patients with newly diagnosed IDDM (Champsaur et al, 1982;Gladisch et al, 1976;Yoon et al, 1979), as well as many anecdotal reports describing the development of IDDM in patients with a recent or concurrent coxsackie B virus infection (Ahmad & Abraham, 1982;Asplin et al, 1982;Jenson et al, 1980;Nigro et al, 1986;Niklasson et al, 1985;Orchard et al, 1982;Palmer et al, 1981;Wilson et al, 1977). The situation is more definitive in animals, where coxsackie B viruses induce a diabetes-like syndrome in genetically susceptible animals, including several strains of mice (Coleman et al, 1973;1974;Toniolo et al, 1982;Yoon et al, 1978) and Patas monkeys (Yoon et al, 1986).…”
Section: Discussionmentioning
confidence: 99%